Effect of Adhesive Variation on the Characteristic of Palm Shells‘ Biomass Briquettes - Kholiq Deliasgarin Radyantho; Selvia Nur Qolbi; Faisal Manta; Doddy Suanggana; Muhammad Iskandar (International Journal of Marine Engineering Innovation and Research, 2023)
Palm oil shells are an example of the residual products of the palm oil processing industry which can be utilized as a new alternative renewable energy source in the form of briquettes. The oil palm shells in this study were first carbonized for 1 hour with a heating temperature in the muffle furnace of 600°C, then crushed and mashed, then kneaded with each variation of adhesive and molded so that the dough can form a cylinder with a diameter of 2 cm and 4 cm high. The average calorific value obtained for cornstarch adhesive, rice flour adhesive and pine resin adhesive were respectively 6634.29 cal/gr, 6702.47 cal/gr, and 7798.31 cal/gr. The average water content in cornstarch adhesive, rice flour adhesive, and pine resin adhesive were 5.1%, 5.0% and 3.7%, respectively. The average values of volatile matter content in the adhesives of cornstarch, rice flour, and pine resin were 30.90%, 31.70% and 60.73%, respectively. The results of this study indicate that any increase in the calorific value will be followed by a decrease in the water content and the varying values of the volatile matter content.